Redescription of the Red Sea gobiid fish Ctenogobiops maculosus (Fourmanoir) and validation of C. crocineus Smith - Kovačić, Marcelo; Bogorodsky, Sergey V.; Randall, John E. (Zootaxa, 2011)
The shrimp-associated gobiid fish Ctenogobiops maculosus, briefly described by Fourmanoir (1955) from one specimen from the southern Red Sea, is redescribed and illustrated with underwater photographs. A diagnosis is given for the closely related C. crocineus Smith 1959, also with underwater photographs. Ctenogobiops maculosus is presently known only from the Red Sea. Ctenogobiops crocineus is wide-ranging from the Red Sea, and Indian Ocean (type locality, Seychelles), to the western Pacific, with records from the Great Barrier Reef and the Ryukyu Islands. The record of C. maculosus from Taiwan by Thacker et al. (2010) is reidentified as C. crocineus, a first record for the island, and their range extension of C. crocineus to Fiji is confirmed.